2023
DOI: 10.48550/arxiv.2302.09210
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How Good Are GPT Models at Machine Translation? A Comprehensive Evaluation

Abstract: Generative Pre-trained Transformer (GPT) models have shown remarkable capabilities for natural language generation, but their performance for machine translation has not been thoroughly investigated. In this paper, we present a comprehensive evaluation of GPT models for machine translation, covering various aspects such as quality of different GPT models in comparison with stateof-the-art research and commercial systems, effect of prompting strategies, robustness towards domain shifts and document-level transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 18 publications
3
37
0
Order By: Relevance
“…• In this analysis, I took a high-level approach to examining the failures of ChatGPT. However, for future investigations, it may be useful to focus on more specific categories of problems, such as sentiment analysis, named entity recognition, translation [27,28], summarization [66], and language ambiguity [47], in order to gain a more detailed understanding of ChatGPT's shortcomings in these areas [49].…”
Section: Discussionmentioning
confidence: 99%
“…• In this analysis, I took a high-level approach to examining the failures of ChatGPT. However, for future investigations, it may be useful to focus on more specific categories of problems, such as sentiment analysis, named entity recognition, translation [27,28], summarization [66], and language ambiguity [47], in order to gain a more detailed understanding of ChatGPT's shortcomings in these areas [49].…”
Section: Discussionmentioning
confidence: 99%
“…Meta's No Language Left Behind translates 200 different languages with high-quality results (Meta, 2022), and Google Translate, as of 2022, supports 133 languages, including 24 low-resource languages (Bapna, 2022). OpenAI's GPT models also emerge as excellent translators by generating context-relevant translation (Hendy et al, 2023). The approach proposed by Jung et al (2023) currently utilizes Google Translate API as well as GPT 3.5, which was shown to be capable of translating student responses with These examples demonstrate the impacts of LLMs and generative AI on automated scoring.…”
Section: Automated Scoringmentioning
confidence: 99%
“…The study also highlighted that GPT-3 achieved a relatively high level of accuracy in translating specialized religious text, with scores comparable to human translations in certain instances. Furthermore, Hendy et al (2023) evaluated GPT in the context of machine translation, exploring various dimensions such as the quality of different GPT models compared to state-of-the-art research and commercial systems, the impact of prompting strategies, robustness in the face of domain shifts, and document-level translation. The results suggested that GPT models demonstrated competitive translation quality for languages with ample resources but had limited capabilities when dealing with languages with scarce resources.…”
Section: Ai and Translationmentioning
confidence: 99%